Toward an Islamic Multicultural Educational Management Paradigm: Developing Humanistic Character in Generation Z - Resti Yulastri; Dinda Auliya Safitri; Halawatul Fitri; Ririn Isnadia (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2026)
This study aims to examine the role of multicultural education in developing the humanistic character of Generation Z and to formulate an Islamic Multicultural Educational Management Paradigm that integrates multicultural values with Islamic educational principles. The study addresses contemporary social challenges, including intolerance, discrimination, digital hate speech, declining empathy, and social polarization among young people in increasingly diverse and digitally connected societies. This study employed a library research approach using an integrative literature review design. Data were collected from scholarly books, peer-reviewed journal articles, policy reports, and other relevant academic sources on multicultural education, Islamic educational management, character education, and Generation Z. The data were analyzed using descriptive-analytical and thematic synthesis techniques to identify conceptual relationships and develop a comprehensive theoretical framework. Multicultural education significantly contributes to the development of tolerance (tasamuh), empathy, democratic attitudes, social responsibility, mutual respect, and appreciation for human dignity. Furthermore, the study demonstrates that these values are closely aligned with Islamic principles, particularly ukhuwah basyariyah (human brotherhood), ta'aruf (mutual understanding), and rahmatan lil ‘alamin (universal compassion). The findings also indicate that multicultural education should not be limited to classroom instruction but should be institutionalized through leadership, organizational culture, governance, and educational management practices. This study introduces an Islamic Multicultural Educational Management Paradigm that positions multicultural education as a governance and institutional transformation framework rather than merely a pedagogical approach. The study advances Islamic Educational Management by providing a conceptual model that integrates multicultural educational principles, Islamic epistemological values, and humanistic character development. This framework offers theoretical and practical guidance for educational institutions seeking to foster socially responsible, inclusive, and ethically grounded Generation Z learners in the digital era.